The Multivariate DCC-GARCH Model with Interdependence among Markets in Conditional Variances' Equations - Marcin Faldzinski; Michal Bernard Pietrzak (Institute of Economic Research (IER), 2015)
The article seeks to investigate the issue of interdependence that during crisis periods in the capital markets is of particular importance due to the likelihood of causing a crisis in the real economy. The research objective of the article is to identify this interdependence in volatility. Therefore, first we propose our own modification of the DCC-GARCH model which is so designed as to test for interdependence in conditional variance. Then, the DCC-GARCH-In model was used to study interdependence in volatility of selected stock market indices. The results of the research confirmed the presence of interdependence among the selected markets.
Keywords: C32; 330; DCC-GARCH model; interdependence; conditional variance